Improving personal and social skills through motor activity supported by gaming technology - Natale Marzullo; Francesco Tafuri (Firenze University Press, 2023)
The new educational systems must take on the responsibility to implement innovative forms of learning. International trends such as Agenda 2030 and the new Framework on LifeComp 2020 dictate the guidelines for teaching and define how pedagogical research should be oriented towards strengthening personal skills, towards a system that allows the acquisition of skills to learn how to learn, to provide valuable help to be more resilient and to finally manage the challenges and changes that life may present. Educational systems must find solutions to implement new forms of learning, capable of guaranteeing individual and social well-being, but above all, capable of including all subjects, especially those who may be excluded because of some disability.   Miglioramento delle abilità personali e sociali attraverso l'attività motoria assistita dalla tecnologia di gioco. I nuovi sistemi educativi hanno il compito di integrare e percorrere nuove strade per implementare delle innovative forme di apprendimento. I trend internazionali come Agenda 2030 e il nuovo Framework sulle LifeComp 2020 dettano le linee guida perché la didattica e la ricerca pedagogica siano orientate verso un rafforzamento delle competenze personali, verso un sistema che consenta l'acquisizione di competenze per imparare ad imparare, per fornire un valido aiuto ad essere più resilienti e a gestire le sfide e i cambiamenti che la vita possa presentare. In quest'ottica i sistemi educativi devono trovare le soluzioni per implementare nuove forme di apprendimento, capaci di garantire il benessere individuale e sociale, ma soprattutto capaci di includere tutti i soggetti, in particolare coloro che dovessero essere esclusi a causa di qualche disabilità.